2009
DOI: 10.1097/mao.0b013e31819679ca
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Longer (8.5 mm) Abutment for Bone-Anchored Hearing Aid

Abstract: We have found the longer abutment to be very successful for the small proportion of patients with troublesome soft tissue overgrowth. We would advocate its use when topical management and surgical intervention have failed to control the skin reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 6 publications
4
48
0
1
Order By: Relevance
“…Soft tissue problems associated with the BAHA have frustrated the otologic surgeon and patient (2,6,7,9). Our experience and hypothesis is that major soft tissue complications such as overgrowth or scarring are most common in obese patients and that a high BMI could identify an increased risk for complications.…”
Section: Discussionmentioning
confidence: 91%
“…Soft tissue problems associated with the BAHA have frustrated the otologic surgeon and patient (2,6,7,9). Our experience and hypothesis is that major soft tissue complications such as overgrowth or scarring are most common in obese patients and that a high BMI could identify an increased risk for complications.…”
Section: Discussionmentioning
confidence: 91%
“…7,10 Similar to our report, these studies also found that use of the longer 8.5 mm abutment reduced the need for additional surgical procedures in most patients. 7,10 Complications specifically associated with use of the longer abutment have not been described in the literature. Although a longer abutment may theoretically increase the torque applied by the processor onto the osseointegrated implant, the commercially available 8.5 mm abutment has been tested and approved by the US Food and Drug Administration, and thus far the incidence of implant loss has not increased.…”
Section: Discussionmentioning
confidence: 92%
“…Our series demonstrated a 36 per cent incidence of previous skin graft failure, while Monksfield et al reported a prior graft failure rate of 29.3 per cent. 7 In contrast, the incidence of skin graft failure in the general population undergoing BAHA placement has been reported as 3-10 per cent. 1,2 These results suggest an association between soft tissue overgrowth and prior skin graft failure.…”
Section: Discussionmentioning
confidence: 94%
“…Only one patient from each surgical group was fitted with the abutment size of the other. The longer abutment has been used with success in patients with thick tissues surrounding the implant, and in those where soft tissue overgrowth was a persistent problem [14]. In the present study there were significantly fewer patients requiring topical steroids in the W or 9 mm group than in the IJ or 6 mm group.…”
Section: Discussionmentioning
confidence: 45%